2015
DOI: 10.2217/nmt.14.45
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does Tobacco Smoking Play in Multiple Sclerosis Disability and Mortality? A Review of the Evidence

Abstract: There is increasing evidence of tobacco smoking as an associative factor in multiple sclerosis (MS). Numerous studies have been conducted investigating the effects of smoking before the onset of MS as well as its impact on disease course. This special report reviews the available evidence and summarizes the contribution of smoking to increased mortality in patients with MS. It also explores some putative mechanisms for the involvement of tobacco constituents in the pathology of MS and the effects of smoking on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Unhealthy lifestyle habits including smoking and alcohol abuse are of major importance as well, according to recent reports on their association with disease progression and survival. 3,11 Further studies should elucidate the particular influences of several comorbidities on the course and outcome of MS, which is important for better clinical care of the individual patient, as well as for developing health system optimization strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Unhealthy lifestyle habits including smoking and alcohol abuse are of major importance as well, according to recent reports on their association with disease progression and survival. 3,11 Further studies should elucidate the particular influences of several comorbidities on the course and outcome of MS, which is important for better clinical care of the individual patient, as well as for developing health system optimization strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Clinicians should be aware of this interplay when managing MS symptoms. Promoting smoking cessation as part of a secondary and tertiary management strategy is, however, vital since smoking has been shown to play a significant role in disease progression ( 33 ), although this may be more difficult in people experiencing pain or depression.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette compounds, such as nicotine and tobacco, cause this problem in the immune system. Researchers have shown that nicotine increases blood flow in the cerebral capillaries and increases the penetration of the solution into the blood brain barrier, and ultimate leakage from the blood brain barrier is suggested to be a factor in the development of MS 31,32 . Another possibility is that some compounds in cigarettes may have direct toxic effects on the central nervous system and cause myelin loss of neurons 33 .…”
Section: Smokingmentioning
confidence: 99%